Hydromagnetic dynamos in rotating spherical fluid shells in dependence on the Prandtl number, density stratification and electromagnetic boundary conditions - ŠOLTIS, Tomáš; ŠIMKANIN, Ján (Contributions to Geophysics and Geodesy, 2014)
We present an investigation of dynamo in a simultaneous dependence on thenon-uniform stratification, electrical conductivity of the inner core and the Prandtl number.Computations are performed using the MAG dynamo code. In all the investigatedcases, the generated magnetic fields are dipolar. Our results show that the dynamos, especiallymagnetic field structures, are independent in our investigated cases on the electricalconductivity of the inner core. This is in agreement with results obtained in previousanalyses. The influence of non-uniform stratification is for our parameters weak, which isunderstandable because most of the shell is unstably stratified, and the stably stratifiedregion is only a thin layer near the CMB. The teleconvection is not observed in our study.However, the influence of the Prandtl number is strong. The generated magnetic fieldsdo not become weak in the polar regions because the magnetic field inside the tangentcylinder is always regenerated due to the weak magnetic diffusion.